PENGEMBANGAN E-BOOK ANTI STUNTING (EBAS) BAGI KADER KESEHATAN MENGENAI PENCEGAHAN STUNTING (Politeknik Kesehatan Kemenkes Bandung, 2021)
Stunting in Indonesia is mostly caused by inadequate nutritional intake for a long time so that children experience difficulties in achieving physical and cognitive development. This is due to low nutritional intake in the First 1000 Days of Life (HPK), poor sanitation, and lack of access to clean water. The provision of information through E-Books can be used to increase the level of knowledge efficiency in preventing Stunting through Health Cadres. The purpose of this research is to produce a health promotion media E-Book Anti Stunting for Health Cadres regarding Stunting prevention. The type of research used is the method of mix methods through a qualitative and quantitative approach with a census sample technique. The result of this study is that it is known that the Anti Stunting E-Book is an educational medium that health cadres want for Stunting prevention materials with 1000 HPK interventions, which in the process of making media prototypes use the ADDIE development model consisting of analysis, design, development, implementation and evaluation. . The validity of the E-Book Media by the material gets a value of 83% in the appropriate category and media experts gets a value of 99% in the very feasible category, while the results of the validity of the material and media by health cadres get a score of 87.6% which is included in the very feasible category. The conclusion of this study is the Anti Stunting E-Book as an educational medium regarding Stunting Prevention with 1000 HPK Interventions.